Somatostatin Receptors and Chemokine Receptor CXCR4 in Lymphomas: A Histopathological Review of Six Lymphoma Subtypes - Juntikka, Tiina; Vaittinen, Samuli; Vahlberg, Tero; Jyrkkiö, Sirkku; Minn, Heikki (Frontiers in Oncology, 2021)
BACKGROUND: Somatostatin receptors (SSTR) and chemokine receptor CXCR4 are expressed in lymphomas, while the abundance is known to be heterogeneous in different subtypes of lymphomas. Targeting tumor cells expressing these receptors might add to therapeutic opportunities while radiolabeled ligands for both imaging and therapy have been developed. The aim of this study was to establish SSTR subtype 2, 3 and 5 and also CXCR4 status immunohistochemically in six different lymphoma subtypes: diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL), mantle cell lymphoma (MCL), mucosa-associated marginal B-cell lymphoma (MALT), Hodgkin lymphoma (HL) and peripheral T-cell lymphoma (PTCL). MATERIAL AND METHODS: This study included a total of 103 lymphoma patients (24 DLBCL, 22 FL, 18 HL, 9 MALT, 20 MCL and 10 PTCL) diagnosed in the Southwest hospital district of Finland during 2010-2019. SSTR 2, 3 and 5 and CXCR4 expression was analyzed immunohistochemically (IHC) in lymphoma samples obtained from local archival Biobank tissue repository. Immunopositivity of each receptor was scored on a four-point scale accounting for staining intensity and proportion of positively stained tumor cells. RESULTS: Of different SSTR subtypes SSTR2 immunopositivity was most common and seen predominantly at the cell membrane of the malignant cells in 46-56% of DLBCL, HL and FL. CXCR4 co-expression was frequently present in these cases. SSTR3 and SSTR5 IHC were negative in DLBCL and FL but in HL SSTR expression was more heterogenous and SSTR3 and SSTR5 positivity was found in cytoplasm in 35% and 25% of cases. 2/4 blastoid MCL variants and one pleomorphic MCL variant had positive CXCR4 IHC whilst all other MCL cases (85%) were negative for all receptors. 30% (n=3) of the PTCL patients had positive SSTR5 IHC and CXCR4. MALT lymphomas were negative for all receptors. CONCLUSION: SSTR2 and CXCR4 are found in DLBCL, FL and HL and co-expression of these receptors is common. Although in general expression of SSTRs and CXCR4 is heterogenous and very low in some subtypes such as MCL and MALT there are also patients with abundant expression. The latter are candidates for trials studying SSTR2 and/or CXCR4 based treatments in the future.